Sustainable Streetscape and Built Environment Designs around BRT Stations: A Stated Choice Experiment Using 3D Visualizations - Adeel, Ahmad; Notteboom, Bruno; Yasar, Ansar; Scheerlinck, Kris; Stevens, Jeroen (Sustainability, 2021)
The incompatibility between the microscale-built environment designs around mass transit stations and stakeholders’ preferences causes dissatisfaction and inconvenience. The lack of a pedestrian-friendly environment, uncontrolled development patterns, traffic and parking issues make the street life vulnerable and unattractive for users, and affect the mass transit usage. How to design the streetscapes around mass transit stations to provide a user-friendly street environment is a crucial question to achieve sustainable transit-oriented development goals. To recognize the specific attributes of streetscape environment relevant in local context of BRT Lahore, this paper presents the results of a visual preference experiment in which nine attributes of built environment were systematically varied across choice sets. Multinomial logit models were set up to identify the preferences of three target groups: BRT users, commercial building users and residents at different locations. The research indicates that not only the road-related factors (bike lane and sidewalk widths, crossings facilities, street greenery) have a significant influence on people’s preference but also that building heights, and the typology of buildings and housing projects around BRT corridor have shaped these preferences. When planning and designing urban design projects around mass transit projects, these significant attributes should be considered.